The Effect of Implementing Financial Accounting Standards (SAK) on the Quality of Financial Reports in Manufacturing Companies in Indonesia - Herlina (Yayasan Pendidikan Belajar Berdikari, 2024)
The purpose of this study is to investigate the impact of Financial Accounting Standards (FAS) on the quality of financial statements in Indonesian manufacturing enterprises. With rising corporate complexity and demands for openness and accountability, the use of SAKs is critical to ensuring that financial statements are relevant, reliable, and comparable. This study takes a quantitative method, collecting data from the financial statements of eight industrial businesses listed on the Indonesian Stock Exchange (IDX) between 2016 and 2020. Multiple regression analysis is utilized to assess the association between SAK application and financial statement quality as measured by relevance, dependability, comparability, and understandability factors. The study's findings give empirical evidence about the significance of using SAK to improve the accuracy of financial statements, as well as recommendations for policymakers, accounting practitioners, and academics.